La Alta Velocidad ferroviaria en la Unión Europea. Su impacto urbano en Francia y España. - Esteban Martín, Víctor (Geographicalia, 2017)
Nowadays, different High Speed Train systems exists in the European Union. Italy and Germany have made good use of their high population densities and their balanced urban networks for having High Speed services that fit harmouniosely whithin the whole train network. After more than 15 years of High Speed Trains in Europe, the first social and economic conclussions about the urban impact of this new way of transport can be seen. Cities served by T.G.V. show a general improvement in their accessibility. However, this may be to the detriment of traditional train and plane services in routes where they are in direct competition with the TGV. In general, councils make the most of the arrival of High Speed Trains for assisting the recovery of degraded areas like station quarters. The presence of the T.G.V. is not considered, by quaternary sector companies, as the most important reason to locate in the area surrounding the station. However, this is an important consideration for companies wishing to conduct business with others located within urban centres along high speed rail links. Business and Congress Tourism may benefit from potentialy greater accessibilty. However, this may reduce the need for people to require overnight accomodation within a particular city due to the increased ability of completing a round trip during the course of a single day.